We are not born submissive how patriarchy shapes women's lives - Garcia, Manon (Princeton Princeton University Press, 2021)
"In the same magazines where women are urged to be free and to have careers of their own, one can also spot advice about the best ways to be an obliging wife and a perfect mother. Literature, film, TV, and the news depict and glorify a specific, sometimes voluntary, sort of female submissiveness that can be a source of pleasure or satisfaction for even the most independent feminist. But this female submissiveness has scarcely warranted attention in philosophy or feminist thought. From a feminist point of view, imagining that women might, in one way or the other choose to try out such submissiveness comes off as anti-feminist or even misogynistic. But are these submissive desires and pleasures at odds with the feminist's independence? In We Are Not Born Submissive, Garcia explains that the feminist agenda has many components but there are (at least) two of which are at the fore: shedding light on the oppression of women qua women, and fighting against this oppression. Studying female submissiveness, therefore, is a feminist undertaking in that it consists of hearing and taking seriously women's experience, of not presuming that they are victims, passive, or perverted. Garcia maintains it is not only possible, but necessary to study female submissiveness without presupposing anything, typically or naturally feminine or anti-feminist in this submissiveness. Using the theoretical framework of philosopher, Simone de Beauvoir and others, Garcia theorizes this fascinating dynamic in its full complexity. By looking at male dominance not from the point of view of those who dominate but from those who submit, Garcia avoids describing the exterior, objective subordination of women. Instead, she is able to examine what exactly it means to be a woman under male dominance, thereby describing the subjective experience beneath domination. It inevitably consists of not starting from the idea that this submission is inherent within women, nor that it is contrary to their nature, or immoral, or the result of a false, oppressed understanding established by the patriarchy. On the contrary
Includes bibliographical references and index.
Keywords: Women--Psychology.